2021
DOI: 10.3390/kidneydial1020015
|View full text |Cite
|
Sign up to set email alerts
|

Combining Diffusion, Convection and Absorption: A Pilot Study of Polymethylmethacrylate versus Polysulfone Membranes in the Removal of P-Cresyl Sulfate by Postdilution On-Line Hemodiafiltration

Abstract: Dialytic clearance of p-cresyl sulfate (pCS) and other protein-bound toxins is limited by diffusive and convective therapies, and only a few studies have examined how to improve their removal by adsorptive membranes. This study tested the hypothesis that high-flux polymethylmethacrylate (PMMA) dialysis membranes with adsorptive capacity increase pCS removal compared to polysulfone membranes, in a postdilution on-line hemodiafiltration (OL-HDF) session. Thirty-five stable hemodialysis patients randomly complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…PMMA membrane is a synthetic polymer membrane with a homogeneous symmetric structure and larger pores on the inner surface. A few studies suggested removing a wide range of proteins by adsorption in addition to diffusion and filtration with hemodialysis using PMMA membranes [12,14]. Our results showed that the removal of β 2 -m by PMMA membranes was mainly due to adsorption (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…PMMA membrane is a synthetic polymer membrane with a homogeneous symmetric structure and larger pores on the inner surface. A few studies suggested removing a wide range of proteins by adsorption in addition to diffusion and filtration with hemodialysis using PMMA membranes [12,14]. Our results showed that the removal of β 2 -m by PMMA membranes was mainly due to adsorption (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…The latter has enhanced adsorptive properties. The reduction ratio for p-cresyl sulfate was higher with the polymethylmethacrylate membrane [70].…”
Section: Adsorptionmentioning
confidence: 83%
“…In the last years, novel PMMA membranes have been improved and adapted for a new renal replacement modality such as online HDF. The new PMMA membranes (e.g., BG-U) appear to be highly effective in reducing p-cresyl sulfate levels when compared to PS membranes [ 70 ]. All these data suggest that the indication of PMMA dialyzers may represent a practical compromise in efficient dialysis treatment.…”
Section: Pmma Can Ameliorate Immunological Impairment During Hdmentioning
confidence: 99%